DAMPAK MOTIVASI DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - - Supriyati (Universitas Trunojoyo Madura, 2012)
The manifestation of trust on tax payers through self-assessment system will be success when voluntary compliance in the society has been established. The fact in Indonesia shows that the degree of the tax payers’ compliance is still low. This research attempts to see the influence of taxpayers motivation and knowledge of tax on the taxpayer compliance. The hypothesis states starts that motivation and knowledge-of-tax influence the taxpayer compliance. Later on, it was stated that motivation influences taxpayer compliance. The hypothesis testing used simple linear regression. Respondents of this study are personal taxpayers whose business is listed on the Tax Services Office (KPP) Tegalsari Surabaya by 46 people, The personal taxpayers who works on STIE Perbanas Surabaya by 44 people, and students of Accounting Department in STIE Perbanas Surabaya by 74 people. The results of statistical regression test showed that motivation was significantly influence taxpayer compliance on personal taxpayer perception but not on the students' perceptions where tax knowledge significantly does influence the taxpayer compliance. In addition, the test of the effect of motivation to knowledge-of-tax variable showed that motivation did not affect significantly to the knowledge-of tax on the perception of personal taxpayer. However it affected significantly to the tax knowledge. Taxpayers tend to avoid tax evasion efforts because it is considered as a criminal act and if it is done it might ruin personal’s or institutional reputation or might hinder business operations. Taxpayer compliance allegedly influence other factors such as the existence of strict sanctions taxes, complicated tax laws, the amount of assistance committed by the financial/tax consultants, or account representative who can facilitate tax compliance.